Long‐term clinical safety of clindamycin and rifampicin combination for the treatment of hidradenitis suppurativa: a strategy to reduce side‐effects, improving patients' compliance. (1st April 2019) - Marasca, C.; Masarà, A.; Annunziata, M.C.; Bettoli, V.; Luciano, M.A.; Fabbrocini, G.
Abstract: Linked Article: Albrecht et al. Br J Dermatol 2019;180 :749–755 .